Diagnostic Accuracy of ELISA Compared to Rapid Diagnostic Tests for Toxoplasmosis: A Systematic Review - Eka Noviya Fuzianingsih; Wiwit Sulistyasmi; Rachmad Bayu Kuncara; Sulastri Sulastri (Academic Hospital Journal, 2026)
Background: Toxoplasma gondii is an obligate intracellular protozoan responsible for toxoplasmosis, a globally prevalent parasitic infection affecting more than one-third of the world’s population. Accurate and timely diagnosis is crucial, particularly for pregnant women and immunocompromised individuals, to prevent severe complications such as congenital toxoplasmosis and encephalitis. The enzyme-linked immunosorbent assay (ELISA) is widely regarded as a reference serological method due to its high sensitivity and specificity. In contrast, rapid diagnostic tests (RDTs) offer practical advantages but show variable diagnostic performance.Method: This systematic review evaluated and compared the diagnostic accuracy of ELISA and RDTs for toxoplasmosis. Literature searches were conducted in PubMed and Google Scholar for studies published between 2015 and 2025. Eligible studies assessed the diagnostic performance of ELISA and RDTs for detecting T. gondii infection in human populations, including sensitivity, specificity, and overall accuracy.Result: Five studies met the inclusion criteria. Across diverse populations, ELISA consistently demonstrated high diagnostic accuracy, with sensitivity and specificity exceeding 90% in most studies. In contrast, RDTs showed lower performance and greater heterogeneity, particularly in individuals with low antibody titers and in immunocompromised individuals. Nevertheless, RDTs provided operational advantages for rapid screening in low-resource settings.Conclusion: ELISA remains the most reliable method for serological diagnosis of toxoplasmosis, while RDTs may serve as complementary tools for initial screening. The integration of both approaches, along with the adoption of advanced ELISA formats such as recombinant antigen-based or Nano-Gold ELISA, may improve early detection and enhance diagnostic capacity across different healthcare settings.